Guidelines-based treatment associated with improved economic outcomes in nontuberculous mycobacterial lung disease. (2nd November 2019) - Marras, Theodore K.; Mirsaeidi, Mehdi; Vinnard, Christopher; Chan, Edward D.; Eagle, Gina; Zhang, Raymond; Wang, Ping; Zhang, Quanwu
Abstract: Background: The prevalence of nontuberculous mycobacterial lung disease (NTMLD) in the US has increased; however, data characterizing the associated healthcare utilization and expenditure at the national level are limited. Objective: To examine associations between economic outcomes and the use of anti- Mycobacterium avium complex (MAC) guidelines-based treatment (GBT) for newly-diagnosed NTMLD in a US national managed care claims database (Optum ® Clinformatics ® Data Mart). Methods: NTMLD was defined as having ≥2 claims for NTMLD (ICD-9 031.0; ICD-10 A31.0) on separate occasions ≥30 days apart (between 2007 and 2016). The cohort included patients insured continuously over a period of at least 36 months (12 months before initial NTMLD diagnostic claim and for the subsequent 24 months). Treatment was classified as GBT (consistent with American Thoracic Society/Infectious Diseases Society of America guidelines), non-GBT, or untreated. All-cause hospitalization rates and total healthcare expenditures at Year 2 were assessed as outcomes of the treatment prescribed in Year 1 after NTMLD diagnosis. Results: A total of 1, 039 patients met study criteria for NTMLD (GBT, n  = 294; non-GBT, n  = 298; untreated, n  = 447). After adjustment for baseline characteristics, GBT was associated with a significantly lower all-cause hospitalization risk vs non-GBT (odds ratio [OR] = 0.53; 95% CI = 0.33–0.85, p  = 0.008), and vs being untreated (OR = 0.57; 95% CI = 0.35–0.91, p  = 0.020). Adjusted total healthcare expenditure in Year 2 with GBT ($69, 691) was lower than that with non-GBT ($77, 624) with a difference of −$7, 933 (95% CI = −$14, 968 to −$899; p  = 0.03). Conclusions: Patients with NTMLD in a US managed care claims database who were prescribed GBT had lower hospitalization risk than those who were prescribed non-GBT or were untreated. GBT was associated with lower total healthcare expenditure compared with non-GBT.